(untitled) - Heather Bateman; Dan Childers; Paige Warren (Environmental Data Initiative, 2018)
This data package is formatted according to the "ecocomDP", a data package design pattern for ecological community surveys, and data from studies of composition and biodiversity. For more information on the ecocomDP project see https://github.com/EDIorg/ecocomDP/tree/master, or contact EDI https://environmentaldatainitiative.org. This Level 1 data package was derived from the Level 0 data package found here: https://portal.edirepository.org/nis/mapbrowse?scope=knb-lter-cap&identifier=641&revision=3 The abstract below was extracted from the Level 0 data package and is included for context: Waterways are often the focus of restoration efforts in urban areas. In arid regions, passive discharge of urban water sources may stimulate the recovery or growth of wetland and riparian features in dewatered or ephemeral aquatic systems. In the greater Phoenix metropolitan area (GPMA), sections of the Salt and Gila Rivers have been the targets of active restoration through seeding, planting, and irrigation. At the same time, revegetation has occurred in some sections of the rivers in response to runoff from urban water sources (e.g., storm drains). This dataset catalogs the results of bird surveys conducted at several locations along the Salt River in and around the GPMA beginning in March 2013. Monitoring locations focus on reaches of the river with different characteristics, including: (1) urbanized with perennial water and actively restored (n=2 reaches), (2) urbanized with perennial water and passively restored (n=2 reaches), (3) urbanized with ephemeral water but not restored (n=2 reaches), and (4) non-urban reference areas with perennial water (n=1 reach). This program expands on bird monitoring that the CAP LTER conducts at other locations in and around the GPMA, and complements herpetological surveys that are performed at these locations along the Salt River where the bird surveys are performed. This is a long-term monitoring effort of the CAP LTER with on-going data collection.